The transmission of Chinese medicine - Hsu, Elisabeth (Cambridge studies in medical anthropology, 2004)
Based on her experience as disciple of a private practitioner, participating in scholarly seminars of a senior Chinese doctor, and studying at a college of Traditional Chinese Medicine, Elisabeth Hsu provides an insider's account of traditional medical education in China, revealing the way in which context of instruction shapes knowledge.